Post first-line dacarbazine or temozolomide in neuroendocrine carcinoma. Issue 6 (June 2020) - Couronne, Thomas; Girot, Paul; Hadoux, Julien; Lecomte, Thierry; Durand, Alice; Fine, Caroline; Vandevoorde, Katia; Lombard-Bohas, Catherine; Walter, Thomas
Abstract : Objective: First-line chemotherapy in metastatic neuroendocrine carcinomas (NECs) is based on etoposide and platinum. However, there is no standard concerning second-line treatment. The objective of this study was to evaluate efficacy and tolerance of dacarbazine or temozolomide in metastatic digestive NEC as post first-line treatment. Material and methods: This study included patients with a metastatic NEC of digestive or unknown primary site. All patients received platinum-etoposide as first-line chemotherapy. Primary endpoint was progression-free survival (PFS). Secondary endpoints were clinical/morphological responses, toxicity, and overall survival (OS). Results: Twenty-seven patients were included: 17 received dacarbazine and 10 temozolomide as post-first line treatments. Median PFS was 3.0 (95%CI (2.2;3.7)) months. There was no significant difference between dacarbazine and temozolomide on PFS. Clinical and morphological responses were found in 12 and 9 patients, respectively. Median OS was 7.2 (95%CI (2.2;12.2)) months. The toxicity profile was that expected with such treatments. Conclusion: LV5FU2-dacarbazine or temozolomide-capecitabine chemotherapies allow a temporary clinical response for almost half of patients and/or a morphological response for a third of patients.